Piezoelectric Energy Harvesting from a Non-ideal Portal Frame System Including Shape Memory Alloy Effect - Tusset, A. M.; Piccirillo, V.; Iliuk, I.; Lenzi, G. G.; Fuziki, M. E.K.; Balthazar, Jose Manoel [UNESP]; Litak, G.; Bernardini, D. (Springer Nature, 2022)
In this work, the investigation of energy harvesting for a U-frame-type (portal frame) structure is presented. The structure is considered as a composite made out of a Shape Memory Alloy (SMA), accounting for a non-ideal DC motor of limited power supply attached to its rigid body. The energy harvesting is carried out using a piezoelectric material (PZT), accounting for a nonlinear electromechanical coupling model. For the behavior of the SMA, a polynomial constitutive model is adopted, which relates the voltage variation to the temperature. Numerical results demonstrate that both PZT and SMA material has a significant influence on energy harvesting. In addition, it is highlighted that the use of SMA makes controlling the vibrations of the structure possible, increasing the harvested energy.
Keywords: Energy harvesting; Non-ideal systems; Piezoelectric devices; Shape memory alloy